The Influence of Protean Career Attitude, Passion for Work, and Self-Management on Proactive Work Behavior in the Millennial Generation - Purnama Yanti Purba; Josep Jeprian Erianto Sihotang; Riski Ikhsan; Renta Srijuna Lumbantobing; Juliani Juliani (Universitas Pendidikan Ganesha, 2022)
This research's background is the phenomenon of drastic changes in the work environment due to the pandemic, the high number of millennial generation employees, and many employees in control of their careers. This study aims to analyze the effect of Protean Career Attitude, Passion for Work, and Self-Management on Proactive Work Behavior in the millennial generation. The number of respondents is 92 people. The research approach used is descriptive. The population in this study were all employees at PT Satria Parang Tritis, totaling 120 employees. The sample used in this study was 92 respondents. The sampling technique is purposive sampling. The method of data analysis is multiple linear regression. The results of the partial study, Protean Career Attitude has a positive and significant effect on Proactive Work Behavior) with a t-count value of 2.485 > t-table 1.986 and a sig value of 0.015 <0.05. Passion For work has a positive and significant effect on Proactive Work Behavior with a value of t-count 4.220 > t-table 1.986 and sig value 0.000 <0.05. Self-Management positively and significantly affects Proactive Work Behavior with t-count value 2.323 > t-table 1.986 and sig value 0.022 <0.05 in generation millennials at PT Satria Parang Tritis. Simultaneously, Protean Career Attitude, Passion For Work, and self-management positively and significantly affect Proactive Work Behavior in the millennial generation at PT Satria Parang Tritis.